The Surface-to-volume Ratio of the Synthesis Reactor Vessel Governing the Low Temperature Crystallization of ZSM-5 - Ana Hidayati Mukaromah; Grandprix Thomryes Marth Kadja; Rino Rakhmata Mukti; Ignatius Redyte Pratama; Muhamad Ali Zulfikar; Buchari Buchari (Journal of Mathematical and Fundamental Sciences, 2016)
Zeolite ZSM-5 is one of major catalysts in petroleum and fine-chemical industries. The synthesis of zeolite ZSM-5 is usually carried out at high temperature above 100 °C using the immense amount of organic structure-directing agents (OSDA). It is interesting to note that fine-tuning the initial gel mixture can be used to enhance the typical slow crystallization rate of ZSM-5. Herein, we report the effect of the surface-to-volume ratio of the reactor vessel to the crystallization of ZSM-5 at low temperature. The surface-to-volume ratio of the reactor vessel could influence the heat-transfer during the synthesis which further governed the crystallization of ZSM-5. It was found that the higher the surface-to-volume of the reactor, the more crystalline of the resulting products. The product with the highest crystallinity exhibited a nearly-spherical morphology composed of smaller ZSM-5 crystallites. This phenomenon allowed the presence of inter-crystallite mesopores which is an advantage for the catalytic reaction using bulky molecules.